2009
DOI: 10.1038/ncb1863
|View full text |Cite
|
Sign up to set email alerts
|

Border-cell migration requires integration of spatial and temporal signals by the BTB protein Abrupt

Abstract: During development, elaborate patterns of cell differentiation and movement must occur in the correct locations and at the proper times. Developmental timing has been studied less than spatial pattern formation and the mechanisms integrating the two are poorly understood. Border cell migration in the Drosophila ovary occurs specifically at stage 9. Timing of the migration is regulated by the steroid hormone ecdysone, whereas spatial patterning of the migratory population requires localized activity of the JAK/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 53 publications
12
110
0
2
Order By: Relevance
“…3,4 Numerous studies have shown that the collective and guided border cell migration requires a number of coordinated signaling activities such as JAK/STAT, JNK, PVR pathways and ecdysone signaling etc. [5][6][7][8][9][10][11][12][13][14] In addition, the apico-basal polarity and DE-Cadherin based adhesion are crucial for the integrity of border cell cluster during its morphogenetic movement. 6,15,16 As developmental cell migration and pathological cell invasion involve common cellular and biological processes, 3,10,[17][18][19][20][21] further investigation of this model system will contribute to unraveling the molecular mechanisms underlying cancer invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Numerous studies have shown that the collective and guided border cell migration requires a number of coordinated signaling activities such as JAK/STAT, JNK, PVR pathways and ecdysone signaling etc. [5][6][7][8][9][10][11][12][13][14] In addition, the apico-basal polarity and DE-Cadherin based adhesion are crucial for the integrity of border cell cluster during its morphogenetic movement. 6,15,16 As developmental cell migration and pathological cell invasion involve common cellular and biological processes, 3,10,[17][18][19][20][21] further investigation of this model system will contribute to unraveling the molecular mechanisms underlying cancer invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In border cells, signaling through the PDGF/VEGF-related receptor (PVR) and the EGF receptor (EGFR) function together to control their migratory speed and direction McDonald et al 2003McDonald et al , 2006. Other signaling cascades, such as steroid hormones and the Notch pathway, also affect border cell migration (Bai et al 2000;Wang et al 2007;Jang et al 2009). Importantly, homologs of these genes and the same signaling cascades in mammals play roles in regulating cell migration and cancer metastasis (Montell 2003;Naora and Montell 2005;Jang et al 2007), demonstrating the relevance of studies of the Drosophila border cells to cancer biology.…”
mentioning
confidence: 99%
“…Strikingly, combined tj knockdown and slbo 2811 RESEARCH ARTICLE Traffic jam in cell migration overexpression could induce precocious BCC migration. This was not observed for BCCs that only overexpress Slbo (Jang et al, 2009;Rørth et al, 2000;Starz-Gaiano et al, 2008) (our own observations). Some of those BCCs with reduced Tj and elevated Slbo were able to complete migration at early-to-mid stage 9, when BCCs have normally only begun migration (Fig.…”
Section: Tj Functions Upstream Of Slbo To Control Bcc Migrationmentioning
confidence: 76%
“…9C). Through a not-yet-fully-understood mechanism, which involves the activation of ecdysone signaling (Jang et al, 2009), the Jak/Stat pathway becomes active, and induces the expression of Slbo in the developing BCC. We speculate that this initiation of Slbo expression triggers a shift in the balance of the factors that leads to a homeostatic feedback loop between Tj and Slbo.…”
Section: Research Articlementioning
confidence: 99%